ENERGY EFFICIENCY IN THE DESIGN AND CONSTRUCTION OF HOTEL AND RESTAURANT FACILITIES - Pogrebnyak, A. V.; Kucher, M. M.; Sabirov, O. V.; Grytsenko, A. V. (Systems and Technologies, 2025)
The article is devoted to one of the urgent problems of Ukraine’s economy, namely, the possibility of reducing energy consumption and increasing the energy efficiency of production activities. The theoretical foundations of energy efficiency, the legislative justification for the implementation of the basic principles of energy-efficient management, the need to use renewable energy sources, innovative materials, technologies, management systems are studied. The advantages of implementing green design, the use of heat recovery systems, modern lighting systems, building materials, automated management system for both buildings as a whole and their individual functioning systems are considered. It is proved that the relevance and necessity of reforming the energy system of Ukraine is one of the top priorities for the state and private business, which will allow to significantly increase the capabilities regarding the prospects of minimizing energy consumption by implementing the necessary energy efficiency measures. The purpose of the article is to analyze current trends in the field of energy efficiency in the construction of hotel and restaurant facilities, to consider practical examples and development prospects in this field, and to provide proposals for the implementation of the considered approaches. The objectives of the study were: to define the basic principles of energy-efficient design; to analyze the use of renewable energy sources; to analyze the use of innovative materials and technologies; to characterize the use of smart, automated building management systems (BMS); to consider the use of green design opportunities; to analyze the need for an energy audit to assess the energy efficiency of buildings. The article concludes with a list of the studied issues and proposals for the representatives of the hotel and restaurant business on their implementation. The introduction of modern lighting, thermal insulation and water drainage technologies contributes to achieving high standards of energy efficiency, which, in turn, increases comfort and safety for hotel and restaurant guests. The development of energy efficiency in the construction of hotel and restaurant facilities is a complex but promising direction. This is not only a matter of reducing costs, but also an important part of the global strategy to combat climate change, which requires us to be responsible in the use of resources and implement innovative technologies to preserve our planet for future generations.